Diagnosis dan Tatalaksana Guillain Barré Syndrome - Grandis Cristagalli; Harahap, Herpan Syafii; Safat Wahyudi; Aulia Dwi Hendriani; Izza Mufida; Muhammad Sutan Maulana; Rike Delya Rizqina (Faculty of Medicine, Universitas Mataram, 2024)
Guillain-Barré Syndrome or GBS is one of the emergency conditions of neurology. Currently, its incidence is relatively low and rare, with a rate of 0.81 to 1.89 of 100,000 people in a year. Guillain-Barré Syndrome or GBS, also known as acute inflammatory demyelinating polyradiculoneuropathy, is a collection of clinical symptoms caused by an acute inflammatory process that attacks the nervous system. The dominant pathogen that causes Guillain-Barré Syndrome (GBS) is Campylobacter jejuni (C. jejuni). Infection with the pathogen Campylobacter jejuni can trigger an immune and humoral autoimmune response that results in nerve dysfunction and the emergence of GBS symptoms. The clinical course of GBS can be divided into several phases, including the progressive phase, plateau phase, and recovery phase. In cases of GBS, it is possible that these factors are involved in the onset of the disease. Some risk factors associated with GBS include viral infections such as Zika virus, influenza virus, and measles-rubella virus. The diagnosis of GBS includes the main symptoms, additional symptoms, cerebrospinal fluid examination, electrophysiological tests, and the exclusion of other diagnoses. The main symptoms include progressive weakness in the extremities accompanied by or without ataxia and areflexia or hyporeflexia in the tendons. The management that can be done includes supportive therapy through the respiratory system. Another treatment option is immunotherapy, with the goal of accelerating disease recovery and reducing the severity of GBS through the immune system.